Comparison of conventional parallel beamforming with plane wave and diverging wave imaging for cardiac applications a simulation study - Tong, Ling (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2012)
When imaging the heart, good temporal resolution is beneficial for capturing the information of short-lived cardiac phases (in particular, the isovolumetric phases). To increase the frame rate, parallel beamforming is a commonly used technique for fast cardiac imaging. Conventionally, a 4 multiple-line-acquisition (4MLA) system increases the frame rate by a factor of 4, making use of a broadened transmit beam to reduce block-like artifacts. As an alternative, it has been proposed to transmit an unfocused beam (i.e., plane wave or diverging wave) for which a large number of parallel receive beams (i.e., 16) can be formed for each transmit. However, to keep the spatial resolution acceptable in these approaches, spatial compounding of overlapping successive transmits is required. As a result, the effective gain in frame rate is similar to that of a 4MLA system. To date, it remains unclear how conventional 4MLA compares to plane-wave or diverging-wave imaging when operating at similar frame rate. The goal of this study was therefore to directly contrast the performance of these beamforming methods by computer simulation. In this study, the performance of 4 different imaging systems was investigated by quantitatively evaluating the characteristics of their beam profiles. The results showed that the conventional 4MLA and plane wave imaging were very competitive imaging strategies when operating at a similar frame rate. 4MLA performed better in the near field (i.e., 10 to 50 mm), whereas plane-wave imaging had better beam profiles in the far field (i.e., 50 to 90 mm). Although diverging-wave imaging had the poorest performance in the present study, it could potentially be improved by optimizing the settings